Implementation of the POAC (Planning, Organizing, Actuating, and Controlling) Management Model in Optimizing Program at the Da'wah Institute of the Islamic University Campus - Imanudin Imanudin; Fitri Yanti; Khomsahrial Romli; Nasor Nasor; Mawardi Mawardi; Sri Ilham Nasution (Empower : Jurnal Pengembangan Masyarakat Islam, 2025)
In the current context, many campus da'wah institutions face challenges in managing effective programmes, often getting caught up in annual routines without a clear direction. This situation leads to low effectiveness and sustainability of da'wah programmes. Therefore, it is important to apply modern management principles such as POAC so that da'wah can be carried out in a systematic and planned manner. This study aims to analyze the implementation of the POAC (Planning, Organizing, Actuating, Controlling) management model in optimizing the da'wah program at the Islamic University Campus Da'wah Institute. The study used a qualitative approach with a case study design, involving the head of the Campus Da'wah Institute, division administrators, and activity participants as research subjects. Data were collected through in-depth interviews, direct observation, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that the da'wah program planning had been carried out systematically through the preparation of a Work Plan and Program Budget based on needs analysis. Organization was effective with a clear management structure and solid inter-divisional coordination. At the implementation stage, a participatory leadership style was able to encourage active involvement of administrators and increase the effectiveness of da'wah activities. Meanwhile, the control function was carried out through post-event evaluations and accountability reports, although weaknesses were still found regarding the consistency of supervision.